Rheumatology ("Internal Medicine". Modul 2) - Berezin, A. E.; Vizir, V. A.; Demidenko, O. V.; Березін, Олександр Євгенійович; Візір, Вадим Анатолійович; Деміденко, Олександр Вікторович (Запорізький державний медичний університет, 2021)
The executive task force is provided for students of 5th courses of medical faculties for helping to study of some topics in the fields of rheumatology diseases incorporated into the discipline «Internal Medicine». There is the information about the most important topics regarding diagnosis of rheumatology diseases. The textbook is addressed to students of 5th courses of medical university for helping to study of internal medicine in the field of rheumatic diseases.